Microhardness of bulk-fill composite materials - Katarina Kelić; Sanja Matić; Danijela Marović; Eva Klarić; Zrinka Tarle (Acta Clinica Croatica, 2016)
The aim of the study was to determine microhardness of high- and low-viscosity bulk-fill composite resins and compare it with conventional composite materials. Four materials of high-viscosity were tested, including three bulk-fills: QuiXfi l (QF), x-tra fil (XTF) and Tetric EvoCeram Bulk Fill (TEBCF), while nanohybrid composite GrandioSO (GSO) served as control. The other four were low-viscosity composites, three bulk-fill materials: Smart Dentin Replacement (SDR), Venus Bulk Fill (VBF) and x-tra base (XB), and conventional control material X-Flow (XF). Composite samples (n=5) were polymerized for 20 s with Bluephase G2 curing unit. Vickers hardness was used to determine microhardness of each material at the surface, and at 2-mm and 4-mm depth. GSO on average recorded significantly higher microhardness values than bulk-fill materials (p<0.001). The low-viscosity composite XF revealed similar microhardness values as SDR, but signifi cantly lower than XB (p<0.001) and significantly higher than VBF (p<0.001). Microhardness of high-viscosity bulk-fill materials was lower than microhardness of the conventional composite material (GSO). Surface microhardness of low-viscosity materials was generally even lower. The microhardness of all tested materials at 4 mm was not different from their surface values. However, additional capping layer was a necessity for low-viscosity bulk-fill materials due to their low microhardness.